Differential Effect of Sex on Outcomes after Radical Surgery for Upper Tract and Bladder Urothelial Carcinoma: A Systematic Review and Meta-Analysis - Mori, Keiichiro; Mostafaei, Hadi; Enikeev, Dmitry V; Lysenko, Ivan; Quhal, Fahad; Kimura, Shoji; Karakiewicz, Pierre I; Egawa, Shin; Shariat, Shahrokh F (The Journal of urology, 2020)
PURPOSE: We assessed the prognostic value of sex differences in upper tract urothelial carcinoma and urothelial carcinoma of the bladder treated with radical surgery. MATERIALS AND METHODS: The PubMed®, Web of Science®, Cochrane Library and Scopus® databases were searched in July 2019 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Studies were deemed eligible if they compared overall, cancer specific, and recurrence-free survival in patients with upper tract urothelial carcinoma and urothelial carcinoma of the bladder. Formal meta-analyses were performed for these outcomes according to sex differences. RESULTS: Overall 66 studies with 100,389 patients with urothelial carcinoma of the bladder and 40 studies with 39,759 patients with upper tract urothelial carcinoma were eligible for review and meta-analysis. Female patients with urothelial carcinoma of the bladder were associated with worse cancer specific survival (pooled HR 1.20, 95% CI 1.10-1.31), overall survival (pooled HR 1.03, 95% CI 1.01-1.05) and recurrence-free survival (pooled HR 1.13, 95% CI 1.02-1.25). In contrast, those with upper tract urothelial carcinoma were not associated with cancer specific survival (pooled HR 0.94, 95% CI 0.89-1.00), overall survival (pooled HR 0.98, 95% CI 0.95-1.01) and recurrence-free survival (pooled HR 0.90, 95% CI 0.78-1.03). CONCLUSIONS: Sex is associated with cancer specific mortality, overall mortality and disease recurrence in urothelial carcinoma of the bladder but not in upper tract urothelial carcinoma. Given the genetic and social differences between the sexes, sex differences may represent a key factor in the clinical decision making process.
Keywords: nádory močového měchýře; review [publication type]; Prognosis; sexuální faktory; karcinom z přechodných buněk; urologické nádory; Cystectomy; Nephroureterectomy; meta-analysis; transitional cell; urinary bladder neoplasms; Disease-Free Survival; prognóza; Humans; Sex Factors; carcinoma; nefroureterektomie; Urinary Bladder Neoplasms; Urologic Neoplasms; Carcinoma, Transitional Cell; přežití bez známek nemoci; lidé; cystektomie